1988
DOI: 10.1530/jrf.0.0820545
|View full text |Cite
|
Sign up to set email alerts
|

Increase of uterine motility and simultaneous decrease of progesterone concentrations in the rat after bilateral ovariectomy at mid-pregnancy

Abstract: Comparison of uterine activities recorded during the control period to those obtained during the two recording periods after ovariectomy (0-30 min and 30-60 min) showed an increase of the amplitude of uterine contractions (P less than 0.005) and a decrease of the interval between two successive uterine contractions (P less than 0.005) and the delay of electrical activities (P less than 0.005). Progesterone treatment (50 mg/kg i.m.) of ovariectomized rats prevented the abrupt fall in plasma progesterone concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 16 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…Potassium channels play an important role in fertility due to their actions on uterine function, adaptation to pregnancy and contractility [ 60 , 61 , 62 ]. Early pregnancy is characterized by the suppression of uterine motility and high concentrations of progesterone, whereas late pregnancy is dependent on increased motility and estrogen during the last 14 days of pregnancy [ 63 ]. Estradiol has a stimulatory effect on potassium channels causing increased excitability, whereas progesterone has an inhibitory effect [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Potassium channels play an important role in fertility due to their actions on uterine function, adaptation to pregnancy and contractility [ 60 , 61 , 62 ]. Early pregnancy is characterized by the suppression of uterine motility and high concentrations of progesterone, whereas late pregnancy is dependent on increased motility and estrogen during the last 14 days of pregnancy [ 63 ]. Estradiol has a stimulatory effect on potassium channels causing increased excitability, whereas progesterone has an inhibitory effect [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…This difference in contractile behaviour may be attributed to the level of progesterone, that would determine the scarce uterine activity seen at mid-term pregnancy (KURIYAMA & SUZUKI, 1976), while its rapid descent at term converts the uterus into a reactive organ (FUCH, 1978;CLABAUT et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…In late pregnancy in rats, progesterone withdrawal, by ovariectomy or by administration of antiprogestational steroid, also causes an increase in uterine contractility (Clabault et al, 1988; Arkaravichien & Kendle, 1992). In our previous study (Arkaravichien & Kendle, 1990), it was shown that progesterone replacement in rats ovariectomized on day 15 of pregnancy could be delayed up to 36 h after ovariectomy, when uteri might have been contracting for quite a long period, without significant reduction in fetal viability.…”
Section: Introductionmentioning
confidence: 99%